Faktor-Faktor yang Mempengaruhi Generasi Milenial dan Z Terjebak Pinjaman Online - Dayanti, Erli; Manurung, Ulfah Nabilah; Putri, Anggi Emalia; Hasyim (Ikatan Da'i Indonesia, 2024)
Online loans are a type of fintech development, service providers provide loans through technology. People make a lot of online loan transactions. The millennial and z generations are the largest online loan takers. Various factors cause the millennial and z generations to get trapped in online loans. Apart from that, online loans can be detrimental to the millennial and z generations if they are trapped in illegal online loans. This research aims to analyze the factors that influence the millennial and Z generations to take online loans. This type of research method is qualitative research in the form of literature study by collecting library data and reading to manage research materials. The data source is secondary data obtained from various writings such as published articles, websites, books and literature from the OJK and other financial institutions. The results of the discussion in this article are that the millennial and z generations are stuck with online loans, influenced by lifestyle factors and financial literacy. A hedonic lifestyle makes the millennial and z generations trapped in online loans. Low financial literacy can mean that the millennial and z generations don't know how to manage their finances, making them trapped in online loans. Keywords :